Analysis on movie performance using wireless / Hasanul Israf Hashim - Hashim, Hasanul Israf (2005)
This paper examines the performance of movie in different format over wireless local area network (WLAN). The movie is access from the server using wireless in a short time period. The format and the performance will be analyzed using tool name Virtual Dub 1.3 to see the performance of three type movie format based on several parameters such as number of frame, frame size, and frame rate to show the advantage and disadvantage for each format. The file formats are Mpeg, Asf and Avi. The method use in this project based on System Development Life Cycle (SDLC), generally include planning, implementing and analysis. The analysis showed the performance of different type of movie format to show the advantages and disadvantages. From the result we can know what the best format to be used. As conclusion, the best format of movie will be choosing based on quality picture or size of file.